2020
DOI: 10.3390/cancers12082281
|View full text |Cite
|
Sign up to set email alerts
|

Elderly Hepatocellular Carcinoma Patients: Open or Laparoscopic Approach?

Abstract: It remains unclear whether the short-term benefits and long-term outcomes of laparoscopic liver resection (LLR) accrue to elderly patients with medical comorbidities. The aim of the present study was to compare the outcomes between LLR and open liver resection (OLR) in elderly patients (≥65 years) with solitary, treatment-naïve solitary hepatocellular carcinoma (HCC). From January 2013 to August 2017, 256 elderly patients with solitary treatment-naive HCC underwent liver resection. All patients were Child–Pugh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…[ 11 , 12 , 20 ] In the treatment of malignant liver tumors, the curative effect of LH is equivalent to that of OH. [ 21 , 22 ] In our study, 61 patients with PLA of different causes and different locations underwent hepatectomy, of which 28 patients underwent LH, and 33 patients underwent OH. There was no significant difference in the operation time between the 2 groups, but the intraoperative blood loss, postoperative hospital stay, numerical rating scale, and overall postoperative complication rate in the LH group were significantly lower than those in the OH group.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 , 12 , 20 ] In the treatment of malignant liver tumors, the curative effect of LH is equivalent to that of OH. [ 21 , 22 ] In our study, 61 patients with PLA of different causes and different locations underwent hepatectomy, of which 28 patients underwent LH, and 33 patients underwent OH. There was no significant difference in the operation time between the 2 groups, but the intraoperative blood loss, postoperative hospital stay, numerical rating scale, and overall postoperative complication rate in the LH group were significantly lower than those in the OH group.…”
Section: Discussionmentioning
confidence: 99%
“…The role of LLR techniques is to reduce the amount of surgical trauma and the degree of physiological disruption to patients. There have been numerous publications detailing the short-term benefits of LLR when applied to a general population [ 10 18 23 24 ]. Previous studies have reported an association between operative time and postoperative morbidity in LLR [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The choice between LLR or open LR (OLR) depended on the preferences of individual patients and their surgeons. The selection criteria for choosing the laparoscopic approach were surgeon-dependent and are described in a previous study [ 10 ]. The indication of OLR included tumor size of greater than 10 cm, except when the tumor was of the pedunculated type; reconstruction of vascular or biliary conduit; proximity to an important vital structure that is deemed difficult to dissect laparoscopically; and invasion to adjacent organs necessitating concomitant resection and reconstruction.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations